The Sustainability of Knowledge-Sharing Behavior Based on the Theory of Planned Behavior in Q&A Social Network Community. (19th June 2021) - Feng, Xin; Wang, Lijie; Yan, Yue; Zhang, Qi; Sun, Liming; Chen, Jiangfei; Wu, Ye
Abstract : With the update and iteration of Internet technology, the socialized Q&A (question-and-answer) platform realizes the cross-border dissemination of knowledge with the main purpose of disseminating and sharing knowledge. Zhihu, as a knowledge-sharing platform that relies on the user-generated content model to maintain operation and the strong willingness of users to share knowledge, plays a key role in the development of the community. Currently, social Q&A platforms are facing problems such as low user participation rate and gradual decrease in the number of active users. It is very important and urgent to explore the factors that affect users' willingness to share knowledge. In response to this problem, this paper builds a theoretical model of the factors that are affecting users' willingness to share knowledge and uses questionnaire research methods to conduct research design and collect sample data and uses methods such as correlation analysis and structural equation modeling to verify the model and hypothesis. The research results show that the theoretical model of planned behavior has strong explanatory power and self-efficacy and material rewards have a positive effect on knowledge-sharing attitudes. Finally, according to some research results, this paper shows that, with the change of time, young people have different needs for knowledge sharing than before, while realizing self-worth through sharing experience, and we also hope to protect own interests and hope that there are more factors to encourage more users to share their knowledge and experience. Therefore, we propose that the platform can use incentive mechanisms to promote knowledge sharing while helping sharers realize their self-worth, improve the existing functions of the platform, or carry out activities to encourage users to participate, so as to achieve the purpose of knowledge sharing and maintain the operation of the Zhihu platform.